ADSORPTIVE REMOVAL OF TRACE CONCENTRATION OF FLUORIDE FROM WATER USING CERIUM LOADED DRIED ORANGE JUICE RESIDUE - Paudyal, Hari; Inoue, Katsutoshi (Journal of Institute of Science and Technology, 2018)
Two adsorbents for fluoride ion removal were developed from dried orange juice residue (DOJR) after loading Ce(III) and Ce(IV) in this study. The characterization of adsorbents was done by an energy dispersive X-ray spectroscopy, X-ray diffraction analysis, electron microscopy and chemical analysis. The experimental results indicated that the fluoride removal efficiency of both the adsorbents was influenced significantly by pH and the optimum operating pH was found to be 4. The equilibrium data were well fitted with Langmuir isotherm model and the maximum adsorption capacity of Ce(III)-DOJR and Ce(IV)-DOJR for fluoride were evaluated to be 0.67 and 1.22 mmol/g, respectively. Leakage of cerium from Ce(IV)-DOJR was negligible for trace concentration of fluoride but it was significant for high concentration of fluoride at pH below 3 resulting fluoride precipitation. Therefore, cerium-loaded DOJR investigated in this study can be considered as an efficient, environmentally benign and promising alternative for the treatment of fluoride contaminated with trace amount of fluoride ion.